Impact of Trade Integration between Tunisia and the European Union on Foreign Direct Investments - Yemmen, Jihene (Journal of Reviews on Global Economics, 2025)
This study investigates the impact of Tunisia’s economic integration particularly through the Free Trade Agreement (FTA) with the European Union (EU) on foreign direct investment (FDI) inflows into the country. The analysis adopts a multidimensional theoretical framework, focusing on key structural determinants of FDI attractiveness such as trade openness, human capital, infrastructure quality, political stability, and macroeconomic conditions. A mixed-method approach is employed, combining a systematic literature review with a two-step econometric modeling strategy. Robust causal inference techniques such as instrumental variables and propensity score matching are used to address potential specification biases and improve the reliability of the findings. The results show that the Tunisia-EU Association Agreement has a positive and statistically significant effect on FDI inflows, increasing them by approximately 12% over the period studied. This finding highlights the role of even sector-specific trade integration (limited to industrial goods) in boosting external capital. This research contributes to the literature on trade agreements by offering robust empirical evidence and provides actionable insights for policymakers regarding trade policy and industrial development strategies in developing economies.